Ternary complexation of benzoic acid with β-cyclodextrin and aminoacids. Experimental and theoretical studies - Méndez, Santiago García (2016)
β-Cyclodextrin (β-CD) is a well-known host molecule used to prepare inclusion complexes. Considering that the three dimensional array of these complexes depends on the inclusion mode of the guest molecule within the β-CD cavity, the development of methods to elucidate their structure is highly desired. The main objective of this work aimed to shed light on the structural and energetic features related to the effect of aminoacids (AA: glycine, valine, isoleucine, arginine and glutamic acid) as third components on the complexation of benzoic acid (BA) with β-CD. In addition, hippuric acid (HA), a structure resembling a BA-glycine conjugate, was included as a model molecule to compare the effect of glycine present as a chemical moiety covalently linked to the guest molecule. Phase solubility analyses were performed to determine the relative binding affinities for binary (BA:β-CD and HA:βCD) and ternary (BA:β-CD:AA) complexes, obtaining the following results: BA:β-CD:AA > BA:β-CD: > HA:β-CD. As part of the structural elucidation of the studied complexes, their spatial configurations were determined by NMR and further characterized applying molecular modeling (i.e., molecular docking and molecular dynamics) techniques. Both approaches evidenced that BA and HA included their aromatic rings in the β-CD hydrophobic cavity, both in binary and ternary complexes. When free aminoacids were present as third components, an enhanced affinity of BA for β-CD was observed, feature that was not evidenced when the aminoacid was covalently bound to the included guest (i.e., HA). Exhaustive structural and energetic analyses are presented to rationalize and support these findings.